RAGAM KONTROVERSI DALAM KAJIAN HISAB-RU’YAH - Achmad Mulyadi Achmad Mulyadi (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2010)
Abstract: In falak study, hisab and ru’yah seems the two key terms that must be keyed to each other. Hilâl observation relies on the basis of astronomy computation. In fact, the accuracy of hisab method should be approved through the use of hilâl observation. However, the study arises various controvercy that cannot be denied. The controvercy of hisab inter-study results the application criteria. Furthermore, the the controvercy of ru’yah argues its effective if it is based on global ru’yah or the local one. The artical is about deeply to eleborate that various controvercies and its today’s existency. Key Words: ru’yah, hisab, wujûd al-hilâl, imkân al-ru’yah dan matla’